Case study on the first immigration of fall armyworm, Spodoptera frugiperda invading into China - Xiao-xu SUN; Chao-xing HU; Hui-ru JIA; Qiu-lin WU; Xiu-jing SHEN; Sheng-yuan ZHAO; Yu-ying JIANG; Kong-ming WU (Journal of Integrative Agriculture)
The fall armyworm (FAW), Spodoptera frugiperda is one of the most damaging crop pests, and it has become major threat to the food security of many countries. In order to monitor possible invasion of this pest into China, a searchlight trap was established in March 2018 in western Yunnan Province, China, where it has served as the “first station” for many pests that have migrated from Myanmar to China. A number of suspected FAW moths were captured and identified by DNA sequencing. The results showed that the FAW moth was first captured on December 11 and formed its first immigration peak in mid-December 2018. DNA detection revealed that the early invading FAW population was the “corn-strain”. The field survey indicated that the pest mainly colonized corn in Pu'er, Dehong and Baoshan areas. Migration trajectory simulation implied that the moths might have mainly come from the eastern area in the mid-latitude region of Myanmar (20–25°N, 94–100°E). This case study confirmed the first immigration of FAW into China, and will be helpful for guiding monitoring and management work to control this pest.